Culinary Tourism Potensial In Palu Bay Area - Idham; Dewa Gede Ari Pemayun, I; Made Rai Sukmawati, Ni (International Journal of Science, Technology & Management, 2024)
Culinary Tourism Potensial In Palu Bay Area. This study aims to determine the level of similarity of culinary tourism potential and support factors among urban villages in the area of ??Teluk Palu. The population in this study were all tourists who visited at 8 urban villages ranging from Tipo Subdistrict Ulujadi to Tondo Sub-District Mantikulore District. Sampling technique using purposive sampling approach is done by selecting informants who are considered able to provide the necessary information. The number of samples is 70 people. In general, infomants enter in cluster 1. There is only one cluster member that entered in cluster 2 and cluster 3. In general the characteristics of culinary tourism availability and supporting factors such as trade activities of goods and services, supporting facilities and infrastructure, transportation support, security as well as social and cultural communication in 8 kelurahan have similarity level. Development of the tourism industry, especially culinary tourism in the coast of Palu Bay in recent years can not be done evenly and maximally in 8 villages. The emphasis in terms of tourism development, especially culinary tourism and its supporting factors still take place partially. Emphasis such as the formation of tourism conscious society and the implementation of 5K has not been implemented evenly and maximally throughout the existing urban village.